Analysis of Factors Affecting Consumer Preferences of the Hotel Syariah in Bandung City - Nurrahman, Ahmad Gemma (Journal of Economicate Studies, 2023)
This study aims to analyze the factors that influence consumer preferences in choosing sharia hotels in Bandung City. The subjects of this study are consumers who have stayed at Sharia Hotels in Bandung City where there are 5 hotels namely Cinnamon Hotel Boutique syariah, Noor hotel Bandung, Narapati Syariah hotel, Ruby hotel syariah, Daarul Jannah Cottage. Sampling using Purposive Sampling technique with data analysis using logistic regression method and descriptive analysis. In this study, factors that influence consumer preferences were found, namely tariffs, location, and halal awareness.